1,10-Phenanthroline and 4,5-Diazafluorene Ketones and Their Silver(I) and Platinum(II) Complexes: Syntheses and Biological Evaluation as Antiproliferative Agents - Leonardo Sandin-Mazzondo; Jesús M. Martínez-Ilarduya; Jesús A. Miguel; Camino Bartolomé; Concepción Alonso (Inorganics)
Using non-classical polyfluorophenyl ligands in Pt(II) complexes and other transition metals such as silver is a promising approach in the search for more effective and safer antitumoral drugs. In this work, a series of chelating N-donor ligands with 1,10-phenanthroline and 4,5-diazafluorene backbones and ketone groups were synthesized (1,10-phenanthroline-5,6-dione, 1; (R/S)-6-hydroxy-6-(2-oxypropyl)-1,10-phenanthroline-5(6H)-one, 2; 4,5-diazafluoren-9-one, 3; 9-hydroxy-9-(2-oxypropyl)-4,5-diazafluorene, 4). The corresponding [Ag(N,N)2]NO3 (1Ag–4Ag) and [Pt(C6F5)2(N,N)] (1Pt–4Pt) complexes were prepared. The stability of these complexes in DMSO solution was studied, showing no dissociation over 48 h for almost all complexes, except 3Pt. The compounds were characterized by NMR (1H, 13C, and 19F), MS, and X-ray diffraction (2, 4, 1Ag, 3Ag, 1Pt, and 3Pt). A study of the cytotoxicity of the compounds in lung carcinoma (A-549) and fetal lung fibroblast (MRC-5) cell lines was performed. Compounds 1, 2, 1Ag, 2Ag, 3Ag, 1Pt, 3Pt, and 4Pt were more active against A-549 cells than cisplatin. Complexes 3Ag and 1Pt showed an acceptable SI and better selectivity than cisplatin, proving that silver(I) complexes and Pt(polyfluorophenyl) complexes are valuable options in searching for new antitumoral drugs.